Role of Neti Karma On The Basis of Nasya Karma For Health Aspect - Goran, Arif Khan; Mishra, Pramod Kumar; Kumar, Mahesh; Bhanot, Neha (International Research Journal of Ayurveda & Yoga, 2021)
Yoga is a group of Physical, Mental & Spiritual practices or disciplines which originated in ancient India. Neti is an important part of Shatkarma (Six procedures). The yogic system of body cleansing techniques. It is intended mainly to clean the air passage. Ayurveda is a system of medicine with historical roots in the Indian subcontinent. Ayurveda therapies and practices have been integrated in general wellness application and in some cases in medical uses. Nasya karma is a term to be applied generally for medicines administered through the nasal route. It is also known as Navana and Nasya karma (Nasal medication). Neti karma (nasal cleansing exercise) and Nasya karma are applied through same route. In this paper evaluate of Neti Karma on the basis of Nasya Karma.